Zarys historii gdańskiej Kliniki Chorób Oczu - Iwaszkiewicz-Bilikiewicz, Barbara (Klinika Oczna / Acta Ophthalmologica Polonica Supplement, 2004)
The author present history of the Department Ophthalmology in Gdansk.